The effects of regulations and supervision on the activities of commercial banks in Zimbabwe - Murandu, Clayton (Midlands State University, 2015)
Banking regulations and supervision is an essential aspect of modern financial systems, seeking crucially to monitor risk-taking by banks so as to protect depositors and the economy as a whole against systemic risk and bank failure. The research involves an investigation on the effects on the activities of commercial banks in Zimbabwe during the dollarization period of (2009-2013). All research findings were obtained from 16 commercial banks and the Reserve Bank of Zimbabwe. The researcher found out that most of the investors are aware of the activity of the RBZ of regulations and supervision on the activities of commercial banks. However, the regulations and supervision had both negative and positive effects on the activities of commercial banks. The negative effect outweighs the positive effects. The researcher found out that supervisory and the regulatory functions of the RBZ have not been effective in curtailing distress in the commercial banks. The results also show that majority of the respondents believed that urgent attention towards verification; processing and settlement of claims filed by depositors of failed banks would help in boosting confidence of the banks’ customers. Therefore, in order for commercial banks to improve profitability it was recommended that commercial banks need to invest in supply side of their macroeconomics through capital expansion and deposit layering activities both at individual bank level and industrial level at large as the demand for bank loans continues to escalate. Therefore,effective bank supervision is important in protecting depositors' funds, avoiding bank failures and installing discipline in the financial sector.